2014
DOI: 10.1186/s13046-014-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase inhibitor II induces apoptosis in glioma cell lines via the p53 signaling pathway

Abstract: BackgroundHistone acetyltransferase (HAT) inhibitors can inhibit proliferation and induce apoptosis in cancer cell lines. The novel cell-permeable p300/CREB-binding protein (CBP)-selective HAT inhibitor HATi II can reduce histone H3 acetylation and induce chromatin condensation in HeLa cells. Here, we examined the effects and mechanism of action of HATi II in glioma cell lines.MethodsCell viability was assessed using the CCK-8 assay. Cell cycle analysis was performed using flow cytometry. Apoptosis was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Xu et al . (2014) suggested that inhibition of HATs may lead to p53 deacetylation, resulting in the transactivation of p53‐regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al . (2014) suggested that inhibition of HATs may lead to p53 deacetylation, resulting in the transactivation of p53‐regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that molecular target pathways, such as the growth factor pathway, Ras pathway, PI3K pathway, p53 pathway, and tumor metastasis invasion pathway, have great potential for the development of meaningful treatment strategies for glioma [33,34]. The p53 pathway is one of the important pathways for the molecular pathogenesis of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advances in surgical resection, chemotherapy and radiotherapy, the prognosis of patients with glioma remains poor, resulting in an overall 5-year survival rate of <10%. Currently, glioma ranks third worldwide as the cause of cancer-associated mortality, after pancreatic cancer and lung cancer (2). The standard therapy for newly diagnosed glioma is surgical resection followed by adjuvant radiotherapy and/or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%